Application of the Problem-Based Learning Model to Improve Students' Scientific Literacy Abilities - Santos Alfrado , Willyam; Yennita, Y; Nelwisman, N; Lestari, Ina (Science Education Department of Mathematics and Natural Sciences Education Faculty of Teacher Training and Education, Universitas Riau in collaboration with the Association of Indonesian Science Educators (PPII), 2024)
Big changes have occurred in the 21st century due to technological advances and rapid developments in various fields. The key to success in facing the challenges of the 21st century is scientific literacy, namely the ability to understand, communicate and apply scientific concepts in real life. However, in reality, practicing 21st-century skills is still rarely done because learning is teacher-centered. This research aims to improve students' scientific literacy skills through a problem-based learning model. The research was conducted in class X MS 4 with 28 students. The research was carried out in two cycles, each consisting of 4 stages: planning, implementation, observation for evaluation, and reflection. From the comparative analysis of scientific literacy abilities in cycles 1 and cycle 2, it was found that scientific literacy abilities in cycle 1 with an average score of 67 in the middle category experienced an increase in cycle 2 with an average score of 77 in the high categories. Based on the research results, it can be concluded that applying the problem-based learning model can improve students' scientific literacy abilities in physics materials.